Russian Science and Technology Foresight – 2030: Key Features and First Results - Alexander Sokolov; Alexander Chulok (Foresight and STI Governance)
This paper reviews national features in the general evolution of science and technology (S&T) foresight over the last decade. Foresight has made a transition from thematic papers and policy briefs to a complex set of methods integrated in the framework of S&T and innovation policy making. Foresight also addresses broad social and economic issues along with conventional S&T problems. It focuses often on interdisciplinary fields and cross-sector problems. It has witnessed the introduction of such new methods as weak signals and wild cards, and it has benefitted from the integration of qualitative and quantitative approaches.